(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Margaret Laurence, an influential Canadian writer is known for her Manawaka novels. In most of her novels she deals with the dilemmas of women relating them to their roots and community. Her fictional world deals with various issues related to identity, survival, ethnicity, multiculturalism and awakening of self. Laurence is a spiritual writer who aspires to transform the existing society into a better and worthier place. In the novel, The Fire-Dwellers, Stacey MacAindra questions the conventional and traditional ways of establishing identity and tries to create an identity of her own. Whenever she tries to surpass the limit she is haunted by sense of guilt that she is unable to be her real self and finally she finds the survival strategy to balance her dual world. The present paper aims to provide a new discourse in finding the social identity by the applying the ideology of Marxist Feminism through the character Stacey MacAindra and her role in the formation of identity.